Extranasopharyngeal Angiofibroma Originating in the Inferior Turbinate: A Distinct Clinical Entity at an Unusual Site - Baptista, Marco Antonio Ferraz de Barros; Pinna, Fábio de Rezende; Voegels, Richard Louis (International Archives of Otorhinolaryngology, 2014)
Introduction The extranasopharyngeal angiofibroma is histologically similar to juvenile nasopharyngeal angiofibroma, differing from the latter in clinical and epidemiologic characteristics.Objectives We present a case of extranasopharyngeal angiofibroma originating in the inferior turbinate.Resumed Report The patient was a girl, 8 years and 6 months of age, who had constant bilateral nasal obstruction and recurrent epistaxis for 6 months, worse on the right side, with hyposmia and snoring. Nasal endoscopy showed a reddish lesion, smooth, friable, and nonulcerated. Computed tomography showed a lesion with soft tissue density in the right nasal cavity. We used an endoscopic approach and found the lesion inserted in the right inferior turbinate. We did a subperiosteal dissection and excision with a partial turbinectomy with a resection margin of 0.5 cm. Histopathology reported it to be an extranasopharyngeal angiofibroma.Conclusion Although rare, extranasopharyngeal angiofibroma should be considered in the diagnosis of vascular tumors of the head and neck.
Keywords: angiofibroma; differential diagnosis; inferior turbinate